2006
DOI: 10.1021/ma0607719
|View full text |Cite
|
Sign up to set email alerts
|

Self- and Collective Dynamics of Syndiotactic Poly(methyl methacrylate). A Combined Study by Quasielastic Neutron Scattering and Atomistic Molecular Dynamics Simulations

Abstract: We have investigated the molecular dynamics of syndiotactic poly(methyl methacrylate) well above the glass transition by combining quasielastic neutron scattering and fully atomistic computer simulations. The incoherent scattering measured by backscattering on a sample with deuterated ester methyl groups has revealed the single-particle motions of hydrogens in the main chain and in the R-methyl groups. Moreover, with neutron spin-echo experiments on the fully deuterated sample we have accessed the collective m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 47 publications
(176 reference statements)
8
47
0
Order By: Relevance
“…We note that shifts in temperature and/or timescale are usually required for a perfect matching of results from MD simulations and real samples. We can mention the cases of orthoterphenyl, 42 polyisoprene, 43 poly(methyl methacrylate), 5,44 poly(vinyl acetate), 45 poly(ethylene propylene), 31 and poly(vinyl methyl ether). 46 Apart from slight differences in the microstructure or in the density, a possible source for this discrepancy could be that the force field used in the simulations was not perfectly calibrated.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that shifts in temperature and/or timescale are usually required for a perfect matching of results from MD simulations and real samples. We can mention the cases of orthoterphenyl, 42 polyisoprene, 43 poly(methyl methacrylate), 5,44 poly(vinyl acetate), 45 poly(ethylene propylene), 31 and poly(vinyl methyl ether). 46 Apart from slight differences in the microstructure or in the density, a possible source for this discrepancy could be that the force field used in the simulations was not perfectly calibrated.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…[1][2][3] Moreover, it has been shown that increasing the size of side groups has a deep impact on the structure and dynamics of polymers. Of particular interest is the family of poly(nalkyl-methacrylates), 2,[4][5][6][7][8][9][10][11][12] where x-ray and neutron diffraction analysis show that nanosegregation occurs between backbone and side groups. The effects of these nanosegregated domains on the local dynamics remain however unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similar behavior has also been found in other polymer systems. 37,70,71 Obviously, the de-Gennes approach proposed for monoatomic simple liquids cannot be applied rigorously to more complex systems such as polymers. As a general conclusion, from this thorough comparison, we can state that not only the self-motions of H-atoms but also the collective dynamics of PEO are well reproduced by the simulated cell.…”
Section: Self-motionmentioning
confidence: 99%
“…The complementary use of these techniques has proven to be an extremely successful route to address a number of similar problems in the field of soft matter. 7,[27][28][29][30][31][32][33][34][35][36][37][38][39] Regarding MD simulations on PEO, a relatively large number of publications can be found in literature. 25,26,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]60 Some of them deal mainly with structural properties, 48,50,51,[53][54][55][56]60 but the local dynamics is also addressed in others; 42,52,57 sometimes the works have been motivated by its use as polyelectrolyte 40,41,…”
Section: Introductionmentioning
confidence: 99%
“…dielectric or mechanical spectroscopy also allow covering such a low-Q limit. On the other extreme, neutron scattering has already been used to investigate the dynamic structure factor at the first structure factor peak Q max , reveling thereby the "genuine" α-relaxation, in a relatively large number of glassforming systems, and in particular in polymers [1][2][3][4][5][6][7][8][9][10][11][12][13]. In fact, the application of neutron scattering techniques to protonated and deuterated samples (addressing thereby the self-motions of hydrogens and the collective response, respectively, see Appendix A) has been key to characterize the dynamics of the structural relaxation at inter-and intra-molecular length scales [8,14,15].…”
Section: Introductionmentioning
confidence: 99%